Interventions to improve the quality of cataract services: protocol for a global scoping review. Issue 8 (11th August 2020) - Yoshizaki, Miho; Ramke, Jacqueline; Furtado, João M; Burn, Helen; Gichuhi, Stephen; Gordon, Iris; Aghaji, Ada; Marques, Ana P; Dean, William H; Congdon, Nathan; Buchan, John; Burton, Matthew J
Abstract : Introduction: Cataract is the leading cause of blindness globally and a major cause of vision impairment. Cataract surgery is an efficacious intervention that usually restores vision. Although it is one of the most commonly conducted surgical interventions worldwide, good quality services (from being detected with operable cataract to undergoing surgery and receiving postoperative care) are not universally accessible. Poor quality understandably reduces the willingness of people with operable cataract to undergo surgery. Therefore, it is critical to improve the quality of care to subsequently reduce vision loss from cataract. This scoping review aims to summarise the nature and extent of the published literature on interventions to improve the quality of services for primary age-related cataract globally. Methods and analysis: We will search MEDLINE, Embase and Global Health for peer-reviewed manuscripts published since 1990, with no language, geographic or study design restrictions. To define quality, we have used the elements adopted by the WHO—effectiveness, safety, people-centredness, timeliness, equity, integration and efficiency—to which we have added the element of planetary health. We will exclude studies focused on the technical aspects of the surgical procedure and studies that only involve children (<18 years). Two reviewers will screen all titles/abstracts independently, followed by a full-text review of potentially relevant articles. For included articles, data regarding publication characteristics, study details and quality-related outcomes will be extracted by two reviewers independently. Results will be synthesised narratively and presented visually using a spider chart. Ethics and dissemination: Ethical approval was not sought, as our review will only include published and publicly accessible information. We will publish our findings in an open-access peer-reviewed journal and develop an accessible summary of the results for website posting. A summary of the results will be included in the ongoing Lancet Global Health Commission on Global Eye Health. Registration details: Open Science Framework (https://osf.io/8gktz ).